Conditioners for raw rice husk substrate to produce strawberry transplants - Signorini, Chaiane Borges; Peil, Roberta Marins Nogueira; Neutzling, Cristiane; Luz, Thiago Freitas da; Grolli, Paulo Roberto (Revista de Ciencias Agrícolas, 2022)
The need to produce domestic strawberry transplants leads to the search for low-cost cultivation media in Brazil. Raw rice husk (CAIN) is an abundant and economical material in the south of the country. This study aimed to evaluate three substrate conditioners (35%) [carbonized rice husk (CRH), vermiculite and the commercial substrate S10®] added to RRH (65%) and their effects on growth, production and quality of strawberry transplants grown on benches with recirculation of nutrient solution, in a greenhouse. The experimental design was in causal blocks with three treatments and four replicates. Two mother plants of the Aromas cultivar were grown on each plot between November/2016 and March/2017. Transplants were classified into groups according to crown diameter (Class 1: 3.0-5.0 mm; Class 2: 5.1-8.0 mm; Class 3: >8.1 mm). Similarly, the number of leaves, leaf surface, fresh and dry mass of leaves and crowns of 10 transplants belonging to each class were evaluated. With the addition of CAC and vermiculite to the substrate, the predominance of class 2 transplants was obtained. The addition of S10 to CAIN increased the total number of transplants, as well as the number of leaf surface transplants and the dry mass of the aerial part of plants, in class 3 transplants, as well as S10 and vermiculite, provided a greater number of propagules produced.